Polymorphism of the tilapia’s populations using restriction endonuclease analysis of mitochondrial DNA - Thanh Binh, Nguyen Thi; Ngoc Thuy, Dinh Thi; Thi, Quyen Dinh; Tuan, Pham Anh (Academia Journal of Biology, 2012)
We analyzed the genetic differentiation among seven populations of the tilapia reared in Vietnam by using restriction fragment length polymorphism (RFLP) of mitochondrial DNA (mtDNA). The PCR products of 12S rRNA from all the above samples were digested with AluI, HinfI, HindIII, PstI, TaqI, BamHI, ClaI, EcoRI, MboI, MspI, RsaI, SacI restriction enzymes. The result showed that eleven enzymes did not cleave and TaqI had identical mono-banded phenotypes. In all samples of populations 16S rRNA, PCR product did not show any restriction sites with twelve above restriction enzymes. The PCR amplification of D-loop gene was digested with AluI, HinfI, MspI, TaqI, AvaII and EcoRI. The enzyme EcoRI did not digested and AluI gave homomorphism. In another enzymes, ten different haplotypes was found, among them the genes types a, e, n could identify the populations R3, R4; the types b, i - to define populations R1, R5, R7; the types d - to determine populations R5; the types k - to specify R1, R5. This field can be developed for practical purpose.